Estimation of some genetic parameters in maize under adequacy and insufficien t water - Wuhaib, Kareema Mohammad; Hadi, Bnan Hassan; Abed, Wajeeha Hassan (Journal of Kerbala for Agricultural Sciences, 2018)
Afield experiment was conducted during two season , spring and fall 2013 in the Field of Crop Science Dept. – College of Agriculture – University of Baghdad . The objective of this experiment are to estimate the genetic parameters , broad sense heritability and co-heritability for several traits of maize ( Zea mays L.) for the synthetic cultivar , Ibaa 5012 , under watered and water stress treatments ( 5 and 10 days intervals) by using randomized complete block design with four replications . Genotypic , phenotypic and environmental variation ( , , ) genotypic and phenotypic coefficient of variation ( GCV , PCV) and broad sense heritability were estimated for ten traits : traits : days to anthesis , days to silking , plant height , ear height , number of leaves , leaf area , days to physiological maturity , dry weight , crop growth rate and grains yield . The results showed that genetic variance for most traits more than environment . GCV values for all traits very closed from PCV , that means the traits were under genetic control .All values of broad sense heritability for both seasons and irrigation treatment are high . The highest value was for the dry weight , crop growth rate, grain yield and number of leaves in two season under irrigated , while in water stress , in addition to these traits the days to physiological maturity . It can conclude that the change in the plant environment due to water stress caused a change in the genetic parameters of the studied traits , especially the change in the amount of genetic variance and the environmental variance , it increased the values of some parameters of the traits and reduced to some others . This led to a change in the values of heritability and co-heritability .